CONTEMPLATIVE POSTMODERN MELANCHOLY: SOLITUDE IN GHOST DOG (1999), ONLY LOVERS LEFT ALIVE (2013), AND PATERSON (2016) - Albuquerque, Washington (Coletivo Cine-Fórum Journal, 2025)
This study investigates the intersection between loneliness in contemporary society and its cinematic representation through the notion of "contemplative postmodern melancholy." It examines the disconnection and introspection of individuals in the face of postmodern superficiality, as well as the role of art, philosophy, and poetry as "bridges" for reconnection. The focus lies on three films by Jim Jarmusch — Ghost Dog (1999), Only Lovers Left Alive (2013), and Paterson (2016) — analyzing how their characters experience loneliness and develop strategies of (re)signification. The theoretical framework combines Fredric Jameson’s (1997) postmodernism, Julia Kristeva’s (1989) conception of melancholy, and Laura Mulvey’s (1975) theory of visual pleasure. Methodologically, the research adopts Manuela Penafria’s (2009) film analysis approach, emphasizing scene decomposition and the visual resources that construct a contemplative atmosphere. Thus, it seeks to understand how Jarmusch’s distinctive style portrays loneliness as a central element of his narratives and aesthetic contemplation as a means of resignification in the face of postmodern emptiness.